Fluorine in medicinal chemistry. - Purser, S; Moore, P; Swallow, S; Gouverneur, V (2008)
It has become evident that fluorinated compounds have a remarkable record in medicinal chemistry and will play a continuing role in providing lead compounds for therapeutic applications. This tutorial review provides a sampling of renowned fluorinated drugs and their mode of action with a discussion clarifying the role and impact of fluorine substitution on drug potency.